Quaternionic Serret-Frenet Frames for Fuzzy Split Quaternion Numbers - Cansel Yormaz; Simge Simsek; Serife Naz Elmas (Advances in Fuzzy Systems)
We build the concept of fuzzy split quaternion numbers of a natural extension of fuzzy real numbers in this study. Then, we give some differential geometric properties of this fuzzy quaternion. Moreover, we construct the Frenet frame for fuzzy split quaternions. We investigate Serret-Frenet derivation formulas by using fuzzy quaternion numbers.